2012
DOI: 10.1002/biof.1009
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of (–)Schisandrin B against 3‐nitropropionic acid‐induced cell death in PC12 cells

Abstract: Huntington's disease (HD) is characterized by the dysfunction of mitochondrial energy metabolism, which is associated with the functional impairment of succinate dehydrogenase (mitochondrial complex II), and pyruvate dehydrogenase (PDH). Treatment with 3-nitropropionic acid (3-NP), a potent irreversible inhibitor of succinate dehydrogenase, replicates most of the pathophysiological features of HD. In the present study, we investigated the effect of (-)schisandrin B [(-)Sch B, a potent enantiomer of schisandrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…On the other hand, the well-established mitochondrial antioxidant and mitoenergetic sparing properties of Sch B make it a particularly promising candidate for promoting brain health. Results from our recent investigation have further demonstrated that Sch B treatment can attenuate the oxidative stress induced by 3-nitroproponic acid, a potent irreversible inhibitor of mitochondrial succinate dehydrogenase that has been used in experimental models of HD, in differentiated PC12 cells and prevent the oxidative stress-induced energy crisis by suppressing the activation of the JNK signaling pathway and the consequent inhibition of PDH [ 76 ], a key bioenergetic enzyme which bridges anaerobic and aerobic brain energy metabolism. This observation supports the role of Sch B in enhancing glucose utilization in the brain.…”
Section: Potential Role Of Schisandrin B As a Hormetic Agent In Prmentioning
confidence: 99%
“…On the other hand, the well-established mitochondrial antioxidant and mitoenergetic sparing properties of Sch B make it a particularly promising candidate for promoting brain health. Results from our recent investigation have further demonstrated that Sch B treatment can attenuate the oxidative stress induced by 3-nitroproponic acid, a potent irreversible inhibitor of mitochondrial succinate dehydrogenase that has been used in experimental models of HD, in differentiated PC12 cells and prevent the oxidative stress-induced energy crisis by suppressing the activation of the JNK signaling pathway and the consequent inhibition of PDH [ 76 ], a key bioenergetic enzyme which bridges anaerobic and aerobic brain energy metabolism. This observation supports the role of Sch B in enhancing glucose utilization in the brain.…”
Section: Potential Role Of Schisandrin B As a Hormetic Agent In Prmentioning
confidence: 99%
“…In addition, Sch B showed neuroprotective effects against focal cerebral ischemic injury in Sprague-Dawley rats [8,9]. Further, Sch B improved paraquat-induced oxidative stress in the rat adrenal pheochromocytoma cell line (PC12 cells) [10,11]. The above studies indicated that Sch B might play a positive role in the therapy of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 85%
“…Oxidative stress has been recognized as a determining factor in causing neuronal cell death in Alzheimer's disease [10,21]. ()Sch B, a dibenzocyclooctadiene derivative isolated from the fruit of Schisandra chinensis, has been shown to induce an antioxidant response in various organs of rodents and in cultured cell lines, including neuronal cells [5,16,22].…”
Section: Discussionmentioning
confidence: 99%
“…a class of non-flavonoid polyphenolics) in the fruit of Schisandra chinensis, was found to produce nonspecific protection against tissue oxidant injury in various organs of rodents, presumably by up-regulating the glutathione redox cycling [5][6][7]. Previous studies have also demonstrated that ()Sch B, a potent stereoisomer of Sch B that amounts to 80% of the stereoisomers [8], increases the resistance of neuronal cells to paraquat-and 3-nitroponoic acid-induced oxidative stress through reducing the extent of oxidant-induced reduced glutathione (GSH) depletion, indicative of enhanced glutathione redox cycling [9,10]. It is therefore of pharmacological interest to examine whether ()Sch B can counteract oxidative stress-induced neuronal cell apoptosis, which has been implicated in the development of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%